1987
DOI: 10.1111/j.1748-1716.1987.tb08134.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adrenoceptor antagonists on vagally induced gastric and duodenal HCO3 secretions in the cat

Abstract: Experiments were performed on chloralosed cats with ligated adrenal glands. The cervical vagi were cut and arranged for electric stimulation. The gastric lumen was continuously perfused, and the secretions of H+ and HCO3- were calculated from pH/pCO2 measurements in the perfusate. Gastric motility was recorded as changes in hydrostatic pressure within the perfusion system. Mucosal HCO3- secretion into a duodenal segment, distal to the papilla of Vater and Brunners gland area, was titrated in situ by a pH-stat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The present results suggest that reflex activation of the SNS, due to a 10% blood loss, releases catecholamines which inhibit duodenal HCO; secretion by an activation of mainly a,-adrenoceptors. These findings are in line with earlier observations in the cat, which suggest that the splanchnic nerves exert a depressive effect on gastroduodenal HCO; secretion via activation of peripheral a,-adrenoceptors (Fandriks I 986, Fandriks & Jonson 1987, Fandriks et al 1987. Bicarbonate secretion is considered to be important in the gastroduodenal mucosal defence (Flemstrom & Turnberg 1984).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present results suggest that reflex activation of the SNS, due to a 10% blood loss, releases catecholamines which inhibit duodenal HCO; secretion by an activation of mainly a,-adrenoceptors. These findings are in line with earlier observations in the cat, which suggest that the splanchnic nerves exert a depressive effect on gastroduodenal HCO; secretion via activation of peripheral a,-adrenoceptors (Fandriks I 986, Fandriks & Jonson 1987, Fandriks et al 1987. Bicarbonate secretion is considered to be important in the gastroduodenal mucosal defence (Flemstrom & Turnberg 1984).…”
Section: Discussionsupporting
confidence: 89%
“…An arterial bleeding of 0.6 ml per IOO g body wt, corresponding to 10% of the total blood volume (Lundin et al 1981), decreases the vagally induced duodenal HCO; secretion via an activation of the splanchnic nerves in the rat (Jonson & Fandriks 1987). Such a reflex activation of the sympathetic nervous system (SNS) is probably induced mainly via unloading of cardiovascular baro-and volume-receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that examined regions of the duodenum devoid of Brunner's glands have demonstrated that bicarbonate secretion is regulated by both extrinsic and intrinsic pathways. These include vago-vagal reflexes (2,7,15,16,23), reflexes within the submucosal plexus of the enteric nervous system (12), C fiber efferent mechanisms (11,29), and inputs from the sympathetic nervous system (5,6,22). The interactions between these neural pathways have also been studied, and the findings suggest that secretomotor reflexes within the submucosal plexus are modified by vagal and sympathetic efferents that provide excitatory and inhibitory inputs, respectively, to submucosal neurons (6,22).…”
Section: Moore Beverley a David Kim And Stephen Vannermentioning
confidence: 99%
“…Activation of sympathetic nerves by applying negative pressure to the lower body, which increases venous pooling and mimics a hypovolaemic situation, decreases gastric bicarbonate secretion in man (0) (n = 6). Data from [25]. [22].…”
Section: Gastric Bicarbonate Secretionmentioning
confidence: 99%